A built-in self-calibrating luminescence sensor based on RhB@Zr-MOF for detection of cations, nitro explosives and pesticides. Issue 33 (20th May 2020) - Yang, Liu; Liu, Yu-Long; Liu, Cheng-Guo; Fu, Ying; Ye, Fei
Abstract : A RhB@Zr-MOF composite with dual-emission properties was demonstrated as a self-calibrating sensor for cations, nitro explosives and nitenpyram. Abstract : A RhB@Zr-MOF composite with dual-emission properties was successfully constructed, which comprises a zirconium-based metal–organic framework and the luminescent dye molecule, Rhodamine B (RhB), embedded via the encapsulation method. The fluorescence intensity ratio of the two emissions was found to be ca. 370 nm/590 nm for RhB@Zr-MOF . The fluorescence intensity values of the two emissions of RhB@Zr-MOF can also be affected by the structures of analytes containing different organic groups. Due to the existence of the dual-emission properties in RhB@Zr-MOF, the relative fluorescence intensity of the emission peaks was introduced as a detection index instead of absolute fluorescence intensity. RhB@Zr-MOF, which possesses the characteristics of a built-in self-calibrating fluorescence sensor, was investigated for detecting cations, nitroaromatics and pesticides. Aside from high sensitivity and selectivity, recyclability is the most important property for sensing pesticides. This work shows that RhB@Zr-MOF can maintain its stability after 5 cycles of detecting nitenpyram, with LOD of 0.2 μM. These results demonstrate that dye@MOFs with dual-emission properties can be employed as multifunctional fluorescence sensors for different types of analytes, and that RhB@Zr-MOF provides a new paradigm for analyte sensing.